Ni/Zn mayered double hydroxide (LDH) micro-nanosystems and their Azorubine adsorption performance - A. Nait-Merzoug, O. Guellati, S. Djaber, N. Habib, A. Harat, J. El-Haskouri, D. Begin and M. Guerioune (Applied Nanosciences, 2021)
A membranous shaped Ni/Zn layered double hydroxide based nanohybrid was obtained using a low-cost template-free hydrothermal process at optimized growth conditions of 180 C for 6 h. The synthesized nanohybrid was structurally, texturally and morphologically characterized using different techniques such as X-ray diffraction, FTIR, XPS spectroscopy, BET analysis and FESEM microscopy. The adsorption performance of our product was estimated through the Azorubine dye removal from synthetic wastewater. We therefore studied the synergic effects of Ni/Zn adsorbent dosage, contact time, pH, adsorbate concentration, stirring speed and temperature on the Azorubine adsorption efficiency. In this investigation, we obtained bi-structure based nanoadsorbent with 54% crystallinity order composed of nickel hydrate and zinc carbonate hydroxides in irregular nanoflake-like mesoporous nanohybrid morphology. Interestingly, it was also revealed to have high specific surface area (SSA) of around 110 m2 g􀀀1 with important textural properties of 18 nm and 0.68 cm3 g􀀀1 average pore size and volume, respectively. Moreover, the adsorption results revealed that this novel Ni/Zn layered double hydroxide (Ni/Zn LDH) was an efficient adsorbent for Az molecule and possesses an adsorptive ability exhibiting a short equilibrium time (60 min) and a high Az adsorption capability (223 mg g􀀀1). This fast removal efficiency was attributed to high contact surface area via mesoporous active sites accompanied with the presence of functional groups (OH􀀀 and CO3 2􀀀). In addition, the Langmuir and Freundlich isotherms were studied, and the results fitted better to the Langmuir isotherm.